Topology optimization of TWB autodoor based on variable density and variable thickness methods - Anping Xu; Yushan Liu; Huan Wang; Yunxia Qu (International Conference on Advanced Technology of Design and Manufacture (ATDM 2010), 2010)
This paper deals with comparative analyses of the variable density method and the variable thickness method which are commonly used in topology optimization of Tailor Welded Blanks (TWBs) autobody. Firstly, mathematic models for both methods are established with density and thickness of elements as design variables. Secondly, Hyper Works-based topology optimization of the door is done using the two methods respectively. The whole blank is segmented according to the optimum cloud map, thus obtaining two or more sub-blanks with complex boundaries and different density or thickness. Finally, the advantages and disadvantages of the two methods are discussed. The results show that the variable thickness method is more suitable for TWB design.